EDUCATION AS A MEANS OF SOCIAL MOBILITY: OPPORTUNITY OR OBSTACLE? - Loso Judijanto; Al-Amin (Adisam Publisher, 2025)
Education has long been recognised as a key means of achieving social mobility, where it can act as a tool that provides opportunities or makes it difficult for individuals to move up in the social strata. This study uses the literature method. The results show that education can provide insights, skills and certifications that enable individuals to obtain better jobs and improve their socio-economic status. Education is also recognised as a factor that helps spread progressive ideas, which contributes to overall social development. However, along with these positive impacts, education also has an ambivalent role. In many cases, unequal and exclusive education systems have hindered social mobility, especially for individuals from marginalised groups. Issues such as high tuition fees, curricula that do not match market needs, and discrimination in education are significant barriers. Thus, to achieve the full potential of education as a tool for social mobility, policies must be designed in such a way that they overcome such barriers and provide equitable access to quality education for all members of society.